Socio-political engagement of contemporary Javanese literature - Margono-Slamet, Yosep B. (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper analyzes four selected short stories in Javanese literature entitled “Durmogati” by Budianto, “Maju Tatu Mundur Ajur” (“Damned if One Does, Damned if One Doesn’t”) by Budiono, “Bojo” (“Wife”) and “Apik Meneng” (“It’s Better to be Silent”) by Harjono which were all published in 2018. In Indonesia, Javanese literature—together with other regional literatures—is a part of or complimentary to Indonesian literature but it has not received much attention at the national level, let alone at the international level. However, Javanese literature has not been less vocal than Indonesian literature. In this article, I will examine the sociopolitical engagements of the four short stories in Indonesian society. Using Phillips’ ethnographic approach and Foucault’s theory of power distribution, I will analyze how the four short stories are related to democracy, people’s power, equality, and corruption in Indonesia after the fall of Suharto as the president of Indonesia in 1998. The analysis shows that the four short stories have significant socio-political engagements in the present Indonesia. The authors of the four short stories discussed in this paper show courage to blatantly criticize those who are in power. As such, the discussion of this essay offers fresh insights about contemporary Javanese literature and its role in the socio-political situation of the country. In the end, this essay will show that these four short stories are not only a reflection of Javanese society in particular and that of Indonesia in general but also as expressions of their authors as key informants about their society, i.e., how they see and think about the society in which they live.